1996
DOI: 10.1037/1082-989x.1.3.300
|View full text |Cite
|
Sign up to set email alerts
|

Types of dissociation and dissociative types: A taxometric analysis of dissociative experiences.

Abstract: This article examined evidence for dimensional and typological models of dissociation. The authors reviewed previous research with the Dissociative Experiences Scale (DBS; E. B. Bernstein-Carlson & F. W. Putnam, 1986) and note that this scale, like other dissociation questionnaires, was developed to measure that socalled dissociative continuum. Next, recently developed taxometric methods for distinguishing typological from dimensional constructs are described and applied to DBS item-response data from 228 adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
601
3
26

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 780 publications
(647 citation statements)
references
References 83 publications
17
601
3
26
Order By: Relevance
“…Specifically, several types of psychopathology, particularly those that are associated with strong biological or environmental influences, have been found to be taxonic. For example, discrete categories have been indicated with regard to schizotypy ( [Korfine and Lenzenweger, 1995] and [Lenzenweger and Korfine, 1992] ), bulimia nervosa (Gleaves et al, 2000), endogenous depression (Haslam & Beck, 1994), and pathological dissociation ( [Waller et al, 1996] and [Waller and Ross, 1997] ). Thus, any attempts to refine psychiatric nosology should not be based on preconceived, or even "expert," notions regarding the categorical or dimensional nature of psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, several types of psychopathology, particularly those that are associated with strong biological or environmental influences, have been found to be taxonic. For example, discrete categories have been indicated with regard to schizotypy ( [Korfine and Lenzenweger, 1995] and [Lenzenweger and Korfine, 1992] ), bulimia nervosa (Gleaves et al, 2000), endogenous depression (Haslam & Beck, 1994), and pathological dissociation ( [Waller et al, 1996] and [Waller and Ross, 1997] ). Thus, any attempts to refine psychiatric nosology should not be based on preconceived, or even "expert," notions regarding the categorical or dimensional nature of psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Taxometric studies have indicated that it is useful to distinguish between "normal" and "pathological" dissociation. Individuals in the "pathological" dissociative class (taxon) can be identified with a brief, 8-item questionnaire called the DES-T [32]. The remaining items may not measure true dissociation-defined as a lack of integration of mental and behavioural phenomena that an individual experiences and memorizes--but measure absorption-like phenomena, i.e., alterations of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Heber et al 56 and Ross and Joshi 38 propose that studies should be done with non-clinical populations, so that their results can be more generally applied to the non-diagnosed population.…”
Section: Resultsmentioning
confidence: 99%
“…According to Waller et al 38 and Martinez-Taboas 39 , pathological dissociation expresses itself through amnesia, depersonalization-derealization, confusion and alteration of identity.…”
Section: Menezes Júnior a Moreira-almeida A / Rev Psiq Clín 2009;36mentioning
confidence: 99%
See 1 more Smart Citation